2017
DOI: 10.15804/kie.2017.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Body Identity: Towards the Subjective Body

Abstract: This paper is a theoretical investigation of body identity. It is an attempt to deepen the analysis of body identity in its subjective aspect, which is framed as a constellation of complex identity senses: the sense of being, continuity of body self in time and space, inner consistency, separateness and bodily limits, as well as the senses of body ownership and agency. All the identified motives of body identity are regarded as pertaining to a special scope in the relationship with the body which produces the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…In conformity with the ESM, multisensory integration provides the foundation for shaping coherent mental representations of the body (Mirucka, 2018). The presented studies have demonstrated that schizophrenia is very closely linked to the manner in which somatosensory experience is organised into mental body representations.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In conformity with the ESM, multisensory integration provides the foundation for shaping coherent mental representations of the body (Mirucka, 2018). The presented studies have demonstrated that schizophrenia is very closely linked to the manner in which somatosensory experience is organised into mental body representations.…”
Section: Discussionmentioning
confidence: 66%
“…According to the hypothetical embodiment model adopted here (Mirucka, 2018), the progression of body experience involves three principal phases: the first and the most basic level is that of neuronal maps, the second is the level of mental representations (including body schema, body image and body awareness), and the ultimate third phase consists in bodily identity senses (cf. Figure 1).…”
Section: The Embodied Subject Model (Esm)mentioning
confidence: 99%
See 1 more Smart Citation
“…The second is body schema, which in turn is based on information from proprioceptive sources [ 40 ]. The last, relatively new theoretical proposition concerns the sense of body states and is based on a wide range of interoceptive experiences [ 41 ]. Each of the paradigms refers to different levels of experiencing one’s own body and also sets out a different methodology for studying these experiences.…”
Section: Methodsmentioning
confidence: 99%